Utilization of Used Cooking Oil in Making Liquid Soap with the Addition of Water Hyacinth (Eichhornia crassipes) Leaf Extract as an Antibacterial - Nababan, Bella Pricilya; Mulmeyda, Rinda; Insyani, Navisya Putri (Chemistry and Materials, 2024)
The frequent disposal of used cooking oil into waterways, along with the proliferation of water hyacinth plants that become invasive in water bodies, contributes to environmental pollution and compromises ecosystem health. One of the effective solutions against various diseases is thorough handwashing with antibacterial soap to eliminate germs and dirt. Therefore, this study aims to investigate the impact of water hyacinth leaf extract addition on the antibacterial activity of cooking oil-based liquid soap. The research employs an experimental approach. Results from pH testing indicate that all liquid soap formulations produced meet the criteria for high-quality liquid soap. Among the variations tested, the formula containing 5% water hyacinth extract exhibited the best foam stability. Regarding antibacterial efficiency, the results suggest that all three samples exhibited weak inhibition of bacterial growth. However, the formula with 10% water hyacinth concentration showed the highest average inhibition zone of 3.46 mm.